2013
DOI: 10.3389/fncir.2013.00088
|View full text |Cite
|
Sign up to set email alerts
|

The CRISP theory of hippocampal function in episodic memory

Abstract: Over the past four decades, a “standard framework” has emerged to explain the neural mechanisms of episodic memory storage. This framework has been instrumental in driving hippocampal research forward and now dominates the design and interpretation of experimental and theoretical studies. It postulates that cortical inputs drive plasticity in the recurrent cornu ammonis 3 (CA3) synapses to rapidly imprint memories as attractor states in CA3. Here we review a range of experimental studies and argue that the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 163 publications
(241 reference statements)
4
93
0
1
Order By: Relevance
“…The tight regulation by the noradrenergic system of synaptic plasticity in the dentate gyrus may serve to support its role as a structure that adapts flexibly to incoming information, and responds best to salient information. Incoming information may be conferred with a “weighting” according to saliency or novelty, that is mediated by ß‐adrenoreceptor activation (Lemon et al, ), thereby enabling the dentate gyrus to engage in “context reset” as postulated for this structure in the encoding of episodic memory function (Cheng et al, ). In line with this, we observed that weak synaptic potentiation is facilitated into LTP in the dentate gyrus by a novel spatial learning experience, and that this facilitation is prevented by antagonism of ß‐adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…The tight regulation by the noradrenergic system of synaptic plasticity in the dentate gyrus may serve to support its role as a structure that adapts flexibly to incoming information, and responds best to salient information. Incoming information may be conferred with a “weighting” according to saliency or novelty, that is mediated by ß‐adrenoreceptor activation (Lemon et al, ), thereby enabling the dentate gyrus to engage in “context reset” as postulated for this structure in the encoding of episodic memory function (Cheng et al, ). In line with this, we observed that weak synaptic potentiation is facilitated into LTP in the dentate gyrus by a novel spatial learning experience, and that this facilitation is prevented by antagonism of ß‐adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the feed forward connectivity from the entorhinal cortex via the perforant path to the CA3 neurons may act as a feed forward pattern association network that is more important than the CA3-CA3 RC autoassociation system (Cheng, 2013). The quantitative properties of pattern association networks are described elsewhere (Rolls and Treves, 1990, 1998; Rolls, 2008).…”
Section: Pattern Separation Of Ca3 Cell Populations Encoding Differenmentioning
confidence: 99%
“…The number of perforant path synapses is sufficiently large that it can generalize given even a partial retrieval pattern, so that the CA3-CA3 connections can then complete the retrieval, given that the recall signal for the perforant path pattern associator is proportional to the square root of the number of perforant path synapses, as shown by Equation 17 of Treves and Rolls (1992). ] The feed forward hypothesis (Cheng, 2013) thus has a strong argument against it of storage capacity, which would be much less (~3600 / 12,000) than that of the CA3-CA3 RC system operating as an autoassociation memory. Another disadvantage of the feed forward hypothesis is that the attractor properties of the CA3-CA3 connections would be lost, and these potentially contribute to holding one or more items simultaneously active in short-term memory (Rolls, 2008; Rolls et al, 2013), and providing a basis for temporal order memory as described in section The Dilution of the CA3 Recurrent Collateral Connectivity Enhances Memory Storage Capacity and Pattern Completion.…”
Section: Pattern Separation Of Ca3 Cell Populations Encoding Differenmentioning
confidence: 99%
“…It has been suggested that the feedforward connectivity from the entorhinal cortex via the pp to the CA3 neurons may act as a feedforward pattern association network that is more important than the CA3-CA3 recurrent collateral autoassociation system (Cheng, 2013). The quantitative properties of pattern association networks are described elsewhere (Rolls and Treves, 1990, 1998; Rolls, 2008).…”
Section: A Theory Of the Operation Of The Hippocampal Ca3 Circuitry Amentioning
confidence: 99%
“…The number of pp synapses is sufficiently large that it can act as a retrieval cue for even an incomplete pattern so that the CA3-CA3 connections can then complete the retrieval, given that the recall signal for the pp pattern associator is proportional to the square root of the number of pp synapses, as shown by Equation 17 of Treves and Rolls (1992). The feedforward hypothesis (Cheng, 2013) thus has a strong argument against it of storage capacity, which would be much less (approximately 3600/12,000) than that of the CA3-CA3 recurrent collateral system operating as an autoassociation memory. Another disadvantage of the feedforward hypothesis is that the attractor properties of the CA3-CA3 connections would be lost, and these potentially contribute to holding one or more items simultaneously active in short-term memory (Rolls, 2008; Rolls et al, 2013), and providing a basis for temporal order memory as described in section Temporal Order Memory in the Hippocampus, and Episodic Memory.…”
Section: A Theory Of the Operation Of The Hippocampal Ca3 Circuitry Amentioning
confidence: 99%